2016
DOI: 10.1902/jop.2016.150707
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic Acid Improves Bone Formation in Extraction Sockets With Chronic Pathology: A Pilot Study in Dogs

Abstract: An infected socket shows delayed healing of the socket wound, and HA, because of its osteoinductive, bacteriostatic, and anti-inflammatory properties, may improve bone formation and accelerate wound healing in infected sockets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 26 publications
3
37
0
3
Order By: Relevance
“…In addition, it was reported that HA stimulated the expression of BMP‐2 and osteopontin (OPN) to regulate the healing process of tooth sockets . These effects may result in bone overgrowth with the socket healing potential immediately after extraction, and HA was intensively transferred with ACS than the gel type used in our previous study …”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…In addition, it was reported that HA stimulated the expression of BMP‐2 and osteopontin (OPN) to regulate the healing process of tooth sockets . These effects may result in bone overgrowth with the socket healing potential immediately after extraction, and HA was intensively transferred with ACS than the gel type used in our previous study …”
Section: Discussionmentioning
confidence: 87%
“…The experimental model used in the present study (extraction socket model with induced chronic pathology) was presented in our previous studies and is suggested to be effective to reproduce clinical situations that can retard the bone healing process and induce severe bone destruction after tooth extraction . Even though our previous research showed an enhanced bone formation by HA application, the extent was not compared with comparable growth factors such as rhBMP‐2 and this was also true for other studies evaluating the effects of HA .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This junction was identified using the method developed by Araújo and Lindhe [12], who reported that newly formed bone could be differentiated from old bone by the detection of primary and secondary osteons and parallel-fibered bone. The following parameters were evaluated for the mesial and distal extraction socket walls for each section using established routines and measured as a percentage: fibrin clots, inflamed granulation tissue, fibrous connective tissue [1314], bone trabeculae, and bone marrow [2315]. Summary statistics (mean±standard deviation) based on recordings from the mesial and distal extraction socket walls of the 4th premolar roots were used to compare diseased and fresh extraction socket sites.…”
Section: Methodsmentioning
confidence: 99%